(untitled) (Proceedings of International Educators Conference, 2023)
The article presents an approach to characterize the modern field of Education based on the integration of knowledge in practice. A two-level system of integration of knowledge, which includes the concepts of knowledge and modern educational objects, is proposed. This will help the integrated knowledge management portal to easily adapt the training to its needs, taking into account the specific characteristics of the educators.